Kinin B1 Receptor Mediated Mechanisms in Hypertension - Parekh, Rohan U (East Carolina University, 2022)
Hypertension continues to cause a burden on the global population as there are growing numbers of patients who present with treatment resistant hypertension. The etiology of hypertension is considered complex and multifactorial and is often difficult to treat even with a myriad of antihypertensive therapeutics. Thus, without novel approaches to combat treatment-resistant forms of hypertension our ability to curtail this burden on the health care system will remain somewhat limited. Evidence has suggested that increased inflammation and oxidative stress, within specific cardiovascular regulatory brain regions such as the paraventricular nucleus (PVN) of the hypothalamus, can result in sympathetic overactivation, a driving force in patient populations with neurogenic hypertension, a form of resistant hypertension. Unfortunately, if blood pressure remains uncontrolled, organ damage can ensue. Our laboratory previously showed increased kinin activity in the PVN in hypertension, however the mechanisms are still not fully understood. Kinin B1 (B1R) receptor activation has been shown to lead to increased proinflammatory and vasoconstrictive effects. Previous studies investigating the therapeutic potential of B1 receptor blockade have provided evidence of its beneficial effects in chronic inflammatory conditions but has not been fully studied in the context of hypertension. Our hypothesis is that B1R blockade reduces blood pressure, inflammation, and end organ damage in angiotensin II-induced hypertension. To explore the role of B1R, we used an in vivo Ang II infusion model coupled with in vitro primary hypothalamic neuron cultures. In the in vitro model we measured the levels of B1R expression, markers of inflammation and oxidative stress, and components of the Renin-Angiotensin System (RAS). In the in vivo model we measured B1R expression, blood pressure, levels of endogenous B1R agonist, proinflammatory cytokines, markers of target organ damage, and interactions between B1R and Angiotensin II type I receptor. Both the in vitro and in vivo findings supported B1R blockade using either a pharmacological antagonist or using genetic deletion was about to attenuate Ang II-induced inflammation, oxidative stress, end organ damage and hypertension. These studies solidify the interaction between the RAS and Kallikrein-Kinin System, specifically through interactions of B1R and AT1R through Ang II. Overall, the findings of these studies establish a critical role for hypothalamic B1 receptor in neurogenic hypertension and its potential as a novel therapeutic target.
Keywords: Kinins, Hypertension